Bundesfinanzierung für Berlin: Ein Patentrezept für den Finanzausgleich ab 2020? - Hubert Schulte (Wirtschaftsdienst, 2014)
Der Länderfinanzausgleich muss neu geregelt werden. Dabei schlagen vor allem die Zahlerländer vor, Berlin aus dem horizontalen Länderfinanzausgleich herauszunehmen und durch den Bund direkt zu finanzieren. Der Autor hält eine solche Sonderregelung für nicht begründbar. Er sieht hier auch verfassungsrechtliche Probleme. Dass ein politischer Kompromiss dadurch leichter würde, hält er für unwahrscheinlich. Der Vorschlag würde das Ausgleichssystem zudem intransparenter und komplizierter machen. – – The federal states Bavaria and Hesse have demanded a change in the system of financial equalisation among the German federal states. One of their demands is that Berlin, as the German capital, should not receive payments from the fiscally strong federal states but rather directly from the federal government. But there are no strong arguments for such a regulation, and it would be contradictory to the constitutional rules on public finance. Moreover, there are additional objections both from a fi nancial and a political point of view which indicate that the proposal by Bavaria and Hesse will not be successful.
Keywords: H72; H73; H77; 330; Berlin; Finanzausgleich; Hauptstadt; Finanzreform; Teilstaat; Deutschland